Fertility treatments and stroke: a scoping review - Aleksandra Pikula; Esther Bui; Ginette Moores; Lindsey Zhang (BMJ Open)
Objectives Fertility therapies are becoming an increasingly common option for conception, but there is little knowledge on the interactions of assisted reproductive technology (ARTs) and stroke in women, and its use among women with a history of stroke. This scoping review aims to examine the current state of knowledge and identify the knowledge gaps regarding: (1) the stroke risk with use of fertility therapy and (2) the safety of fertility therapy among stroke survivors, to help guide future research and clinical practice.Design The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) checklist for scoping reviews was followed.Data sources MEDLINE (Ovid), Cochrane Central Registry of Controlled Trials (Ovid), EMBASE (Ovid), Medline, ClinicalTrials.gov and International Clinical Trials Registry Platform were searched through 20 June 2023.Eligibility criteria for selecting studies All observational studies pertaining to use of fertility and stroke in humans over the age of 18 were included in this review.Data extraction and synthesis Title and abstract and subsequent full-text review were performed by two independent reviewers in duplicate. A narrative synthesis of final articles for data abstraction is presented.Results 10 studies met inclusion criteria. The only meta-analysis that was included could not estimate the risk of stroke among all individuals undergoing fertility therapy due to lack of high-quality prospective cohort studies. There was only one prospective cohort that examined pregnancy among stroke survivors. Among the 32 pregnancies, one was conceived through in vitro fertilisation (IVF), although the details regarding stroke type, time since stroke, medications and IVF protocol were not specified. Therefore, the safety and effectiveness of ART among stroke survivors is currently unknown.Conclusion In this comprehensive review of existing fertility therapy science and stroke risk, we identify a large knowledge gap and a major scientific need for a systematic approach and prospective studies to better inform the risk of stroke during fertility therapy, especially among stroke survivors. Understanding this risk and developing treatment strategies serves to better inform women and healthcare providers as more women with a history of stroke seek and contemplate fertility therapy.Trial registration number DOI 10.17605/OSF.IO/PHQ4X